Surgical shortening of the lower limb in gigantism due to congenital arteriovenous fistula - Nin Vivo, Esteban; Praderi, Raúl (Cirugía del Uruguay, 2020)
The paper refers to a case of partial gigantism of the lower limb, caused by congenital arteriovenous fistula. Following a treatment of the varicose lesions and the interruption of sorne shunts, the skeleton was shortened at the leg level, using Müller's technique,.. which permitted a rapid recovery and eliminated the problems derived from long immobilizations.